2022
DOI: 10.3390/jcm11133769
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir in Very Old Patients (≥80 Years) Hospitalized with COVID-19: Real World Data from the SEMI-COVID-19 Registry

Abstract: (1) Background: Large cohort studies of patients with COVID-19 treated with remdesivir have reported improved clinical outcomes, but data on older patients are scarce. Objective: This work aims to assess the potential benefit of remdesivir in unvaccinated very old patients hospitalized with COVID-19; (2) Methods: This is a retrospective analysis of patients ≥ 80 years hospitalized in Spain between 15 July and 31 December 2020 (SEMI-COVID-19 Registry). Differences in 30-day all-cause mortality were adjusted usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
0
11
0
2
Order By: Relevance
“…Our findings of an independent mortality benefit from remdesivir in hypoxic COVID-19 inpatients coincides with findings of the Adaptive COVID-19 Treatment Trial (ACCT)-1 randomized controlled trial, but not the DisCoVeRy trial, negative findings of the SOLIDARITY trial, and a 2021 meta-analysis [ 70 ]. More recent observational studies and analyses have shown hospital mortality benefits with remdesivir therapy in the Premier Healthcare Database [ 71 ], a reanalysis of the ACCT-1 trial [ 72 ], Danish and Italian cohort studies [ 73 , 74 ], and an elderly Spanish cohort [ 75 ], although studies in the elderly population of US veterans hospitals have not detected an associated reduction in mortality [ 76 ]. Consistent with several earlier studies of tocilizumab, usually given with corticosteroids [ 77–80 ], and a Dutch randomized trial of tocilizumab early in the hospital course of hypoxic COVID-19 patients [ 81 ], we also observed an independent mortality benefit associated with tocilizumab treatment in hypoxic COVID-19 inpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of an independent mortality benefit from remdesivir in hypoxic COVID-19 inpatients coincides with findings of the Adaptive COVID-19 Treatment Trial (ACCT)-1 randomized controlled trial, but not the DisCoVeRy trial, negative findings of the SOLIDARITY trial, and a 2021 meta-analysis [ 70 ]. More recent observational studies and analyses have shown hospital mortality benefits with remdesivir therapy in the Premier Healthcare Database [ 71 ], a reanalysis of the ACCT-1 trial [ 72 ], Danish and Italian cohort studies [ 73 , 74 ], and an elderly Spanish cohort [ 75 ], although studies in the elderly population of US veterans hospitals have not detected an associated reduction in mortality [ 76 ]. Consistent with several earlier studies of tocilizumab, usually given with corticosteroids [ 77–80 ], and a Dutch randomized trial of tocilizumab early in the hospital course of hypoxic COVID-19 patients [ 81 ], we also observed an independent mortality benefit associated with tocilizumab treatment in hypoxic COVID-19 inpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale cohort studies on remdesivir-treated patients with COVID-19 have reported improved clinical outcomes; however, the relevant available regarding older patients remain limited. Nevertheless, a retrospective study assessed the potential bene t of remdesivir in ≥ 80-year-old patients hospitalized with COVID-19 who were unvaccinated [25]. In these patients, remdesivir use remained associated with a lower 30-day all-cause mortality rate after adjustments for age, sex, and low mortality-related variables.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of RDV efficacy and safety among immunocompromised populations has come from cohorts or case series, highlighting the potential of a combination of antiviral therapies or prolonged courses of RDV ( Table 1 ) with variable results [ 32 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. Persistent infection in immunocompromised patients remains a concern, as it seems to drive virus evolution and the selection of new variants [ 84 ]; hence, experience of individualized successful treatment is necessary.…”
Section: Special Populationsmentioning
confidence: 99%
“…Nonetheless, recent data have shown that RDV-associated reduction in mortality in hospitalized cancer patients was consistently observed across all variants of concern prior to B4/5 [ 85 ], while its use reduced re-admission in immunocompromised patients [ 86 ]. The available RWE in special populations is summarized in Table 1 , including patients with chronic liver disease [ 77 , 87 ], those prone to liver damage [ 79 ], the pediatric population [ 75 , 76 , 88 ], and very elderly [ 78 ].…”
Section: Special Populationsmentioning
confidence: 99%